Peningkatan Pengetahuan tentang Pemenuhan Gizi Balita di Rw 04 Kelurahan Medono Kota Pekalongan - Ni'matul Ulya; Pedvin Ratna Meikawati (LPPM Akbid Harapan Ibu Pekalongan, 2020)
Balita means children under 5 years old. The consumption of good and sufficient nutrition often cannot be fulfilled by a child due to external and internal factors. Therefore, as parents, we must also be democratic in order to serve food that is indeed the child's interest. Good nutrition intake plays an important role in achieving optimal body growth. And optimal body growth also includes brain growth that really determines one's intelligence. The food that consumed by the children can be influenced by the knowledge and attitudes of mothers and the support of family and the environment. The knowledge and attitude of the mother will affect food intake in the family, especially children. The purpose of this community service activity is to provide knowledge related to toddler nutrition to mothers who have toddlers in the Medono Village. The method used is education through lectures, questions and answers and discussions. The results obtained by mothers' knowledge regarding the fulfillment of toddler nutrition increased. Before education, 50% of knowledgeable mothers and 80% after being educated. In this activity a commitment was also reached, namely mothers who have babies and toddlers are willing to provide exclusive breastfeeding and are willing to provide MP-ASI which are rich in nutrition